Social Media Network Analysis on Twitter Users Network to the Pension Plan Policy - Al Fauzi Rahmat; M. Rafi (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2022)
This article scrutinizes the network of Twitter users on the dissemination of tweets on the Old-Age Guarantee policy in Indonesia. A qualitative method with social media network analysis approach was used. Then, data sources were obtained from Twitter social media through #JHT_JokowiHarusTurun, #jaminanharitua, and #JHT. Furthermore, to manage data source, NVivo 12 plus software was used to analyze qualitative data from Twitter social media – including dissemination rate of tweets, followed by geographical map tweet stream, Twitter user’ network pattern, sentiment proportion, as well as words frequencies. Our results indicate that there are networks found from Twitter users with some account backgrounds in politicians, political parties, governments, online news media, actors and also cultural practitioners who participate in disseminating tweets. Even this network generated the significant distribution patterns and sentiments to a moderately negative value, coupled with pleasantries that are echoed between protests and support by words cloud to this movement. Overall, our research contributes to better understanding of how social media-promoted collective protest movements have the power to impact public opinion and policy and that their evolution is unexpected.